The Production Guide for the Zarqaliyya (Universal Astrolabe) in the Work of Abu al-Hasan al-Marrakushi - Bir, Atilla; Bütün, Saliha; Kaçar, Mustafa; Akın, Adem (İlmi Etüdler Derneği (İLEM), 2020)
One of the greatest astronomers of the 13th century, Abū ʿAlī al-Ḥasan al-Marrākushī is the author of Jāmiʿ al-mabādī’ wa-l-ghāyāt fī ʿilm al-mīqāt (An A to Z of Astronomical Timekeeping) which includes the production and operation guides for many astronomical instruments. This study translates the production guide Zarqāliyya, examines the working principle of this instrument, and presents a mathematical interpretation for current readers. A standard astrolabe provides measurements by means of disks produced separately for the different latitudes. The particular disk we examine in this article was developed by the Andalusian astronomer al-Zarqālī (d. 493/1100), is named zarqāliyya, and is known as ṣafīḥa in the West. This disk is peculiar to Islamic astronomy and enables measurement for any latitude. At present, this astrolabe is qualified as universal for being operational independent of latitude. Marrākushī’s discussion of this universal disk zarqāliyya in his time is an epitome for the understanding of the transmission and circulation of knowledge in the scientific environment of Islam, and the current article evaluates this aspect. This article includes the subject and importance of Marrākushī’s monumental work, its modern presentations, and the mathematical explanations of the universal astrolabe’s stereographic projection. It additionally provides the formulations necessary for constructing this astrolabe and presents drawings based on these relations using the Paris edition of the manuscript registered as Or. No.2507-2508 in the National Library of France. The stars and coptic months engraved on the instruments are presented as tables. Lastly, this study includes an annotated translation by comparing the different editions of the manuscript.
Keywords: Marrākushī; Zarqālī; Zarqāliyya; Astrolabe; İlm al-mīqāt; Şafīḥa; Universal disk; Astronomical Instruments